2011
DOI: 10.1126/scitranslmed.3002445
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Cardiac Conduction Block and Defibrillation with High-Frequency Electric Field

Abstract: Electrical impulse propagation is an essential function in cardiac, skeletal muscle, and nervous tissue. Abnormalities in cardiac impulse propagation underlie lethal reentrant arrhythmias, including ventricular fibrillation. Temporary propagation block throughout the ventricular myocardium could possibly terminate these arrhythmias. Electrical stimulation has been applied to nervous tissue to cause reversible conduction block, but has not been explored sufficiently in cardiac tissue. We show that reversible pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 40 publications
3
34
0
Order By: Relevance
“…Other work employing AC fields with similar frequency ranges also yielded induction of ventricular fibrillation (VF) [10], [13], continuous entrainment [14][16] and hemodynamic collapse [14][16] without observing any extended APD. In a concurrent study recently published, Tandri, et al have shown the ability of sinusoidal electric fields in the 20 Hz–2 kHz frequency range to produce reversible conduction blocks in several models (including monolayers and whole hearts) through inhibition of excitability by prolonged APD [9]. Using field stimulation of the whole culture or organ, complete conduction blocks were achieved for durations of up to one second.…”
Section: Introductionmentioning
confidence: 96%
“…Other work employing AC fields with similar frequency ranges also yielded induction of ventricular fibrillation (VF) [10], [13], continuous entrainment [14][16] and hemodynamic collapse [14][16] without observing any extended APD. In a concurrent study recently published, Tandri, et al have shown the ability of sinusoidal electric fields in the 20 Hz–2 kHz frequency range to produce reversible conduction blocks in several models (including monolayers and whole hearts) through inhibition of excitability by prolonged APD [9]. Using field stimulation of the whole culture or organ, complete conduction blocks were achieved for durations of up to one second.…”
Section: Introductionmentioning
confidence: 96%
“…We have previously investigated alternating current as an alternative waveform to defibrillate, 27,28 but skeletal muscle activation was increased. We noted, however, that the longer duration of AC would allow skeletal muscle to be gradually tetanized before a standard biphasic shock.…”
Section: Discussionmentioning
confidence: 99%
“…The study by Tandri et al [113] used sustained kilohertz-range alternating current (AC) fields for arrhythmia termination. Termination of arrhythmia with AC fields has been attempted previously in simulations [81][82][83] with limited success; the frequencies used in these studies were, however, substantially lower.…”
Section: Model-based Innovation To Improve Arrhythmia Termination By mentioning
confidence: 99%